The performance study of oil plam bunch infield collection and evacuation transport system: a case study at Kledang Sayong and Ulu Remis Estates / Nurazlin Yusseri - Yusseri, Nurazlin (Faculty of Plantation and Agrotechnology, 2018)
In oil palm plantation, the loading of FFB became recently a problem due to labour shortage in Malaysia. To overcome this problem, about 99.9% mechanize have been offered to all plantation field for loading the FFB collection and evacuation from field to ramp. Unfortunately, there are many plantations still used conventional transport system. The aim of the study is to investigate the performance of oil palm bunch infield collection and evacuation transport system. The finding is shows that mechanize transport system for loading FFB from field to ramp are required replacing the conventional transport system. The result also showed that there has a significant different to performance of field efficiency, time-consuming and cost operation management between conventional and mechanization transport system. The data retrieved from study motion on field was analysed by using SPSS Statistic on One-Way Anova calculation method. According to the analysis of performance field efficiency and calculation of machinery costing, the result proved that mechanical buffalo and compact tractor are suitable to replace the wheelbarrow and 8MT lorry for infield collection and evacuation of FFB. This is due to productivity of mechanical buffalo and compact tractor can be achieved to 10.87 MT and 35.84 MT. The use of the mechanization transport system for mechanical buffalo and compact tractor could be saving to 79% while for MTG could be saving to 45.50% of the cost of FFB infield collection and evacuation transport by conventional system. Conclusively, the outcome of study can contribute to gain early income and improve the quality of FFB.